Particle Swarm Optimization for Operating Theater Scheduling Considering Medical Devices Sterilization - Beroule, Benoit; Grunder, Olivier; Barakat, Oussama; Aujoulat, Olivier; Lustig, Helene (Swarm Intelligence Based Optimization, 2016)
The operating theater scheduling problem is one of the main hospital sector issues of today’s world. Indeed, numerous papers dealing with this subject may be found in the literature. However, the synchronization between the pharmacy (providing the surgical devices and medicines) and the operating theater is rarely studied. Nevertheless, the importance of the pharmacy keeps growing because of the creation of numerous hospital groups composed of several hospital complexes sharing a central pharmacy. In this paper, we focus on the sterilization cycle of the surgical devices to provide operating theater scheduling methods taking into account pharmacy issues. We present exact methods with a mixed integer linear programming model to determine optimal schedules as well as approximate solutions with a particle swarm optimization based method to solve the most complex cases. These modelings provide interesting schedules using few quantities of surgical devices boxes even when considering many procedures. With this study we hope to lay the foundations of a transverse logistics unifying the operating theater and the pharmacy in a multi-site context.